Biomimetic Mechanism of Action of Fluoridated Toothpaste Containing Proprietary REFIX Technology on the Remineralization and Repair of Demineralized Dental Tissues: An In Vitro Study - Vilhena, Fabiano Vieira; de Oliveira, Sonia Mariza Luiz; Matochek, Marcelo Henrick Maia; Tomaz, Pedro Luiz Santos; Oliveira, Thales de Sá; D’Alpino, Paulo Henrique Perlatti (European Journal of Dentistry, 2020)
Objectives This in vitro study aimed to characterize the mineral content and surface and cross-sectional morphology of enamel and dentin tissues treated with a 1450 ppm fluoride-containing toothpaste with REFIX technology.Materials and Methods Bovine enamel blocks (n = 5) were obtained (4 × 4 × 6 mm), demineralized (artificial caries lesion), and treated (pH cycling and brushing with the toothpaste). During the pH cycling, which lasted for 7 days (demineralization and remineralization took 6 and 18 hours, respectively), the enamel was brushed for 5 minutes using an electric toothbrush before being immersed in a remineralizing solution. The dentin blocks were acid-etched for 2 minutes (0.05 M citric acid, pH 1.8) to expose the dentinal tubules (n = 5). Morphological analysis of the dentin was performed immediately and after 7 days of brushing with the dentifrice, and compared with the control group. The specimens were then cross-sectioned. The surface and cross-sectional micromorphology were assessed using scanning electron microscopy (SEM). The elemental analyses (weight%) were determined with an energy-dispersive X-ray spectroscopy (EDS).Results The toothpaste with REFIX technology remineralized and repaired the surface enamel effectively. The elemental analysis also demonstrated that treating the enamel with the toothpaste formed a silicon-enriched mineral layer on the enamel surface. Elemental analysis of the enamel cross-sections showed that the toothpaste induced a mineral change. The results were also consistent in the dentin, where the dentinal tubules were progressively occluded until there was complete occlusion after 7 days.Conclusions We prove the biomimetic mechanism of action of fluoridated toothpaste containing proprietary REFIX technology for obtaining silicon-enriched, remineralized and repaired dental tissues.
Keywords: enamel; dentin; tooth remineralization; toothpaste; microscopy; electron; scanning